Destiny's consul : America's ten greatest presidents - Riccards, Michael P. (Rowman & amp ;, 2012)
In Destiny's Consul: America's Greatest Presidents, presidential scholar Michael P. Riccards provides a concise introduction to the lives, presidencies, and personal qualities of ten great individuals whom Riccards argues are our greatest presidents. It will be of interest to anyone interested in the presidency of American history.